ChatGPT in Science Education: A Visualization Analysis of Trends and Future Directions - Festiyed, -; Tanjung, Yul Ifda; Fadillah, Muhammad Aizri (JOIV : International Journal on Informatics Visualization, 2024)
ChatGPT, as one of the products of artificial intelligence (AI)-based technology, has shown significant potential in science education. This study aims to analyze the development trends and focal points of ChatGPT research, especially in science education from the Scopus database in 2022-2024. This study used Bibliometric analysis which is a quantitative and qualitative evaluation technique of documents in a database. The search method was carried out with the Dimensions and Publish or Perish (PoP) databases using Scopus and data visualization using VOSviewer. Searches were conducted on article titles, abstracts, and keywords at once (TITLE-ABS-KEY) with the keywords "ChatGPT" and "science education". The results of the bibliometric analysis showed a significant increase in the number of ChatGPT-related publications in the field of science education, with several key topics taking center stage, such as pedagogical adaptation, AI-based learning, and evaluation of technology effectiveness in the teaching and learning process. Visual analysis using VOSviewer identified a clustering of research covering the integration of ChatGPT in the science education curriculum, the role of AI in facilitating collaborative learning, and the impact of using ChatGPT on student motivation and learning outcomes. This suggests that the use of AI, particularly ChatGPT, in science education is a growing area of research with significant potential impact. This research provides a comprehensive overview of recent developments in the use of ChatGPT in the field of science education and provides insights for future research.